Performance Enhancement of Underwater Acoustic OFDM Communication Systems - El-Mahallawy, Mohamed; TagEldien, Adly S.; Elagooz, Salah S. (Wireless personal communications, 2019)
The supported bandwidth of the underwater communication systems is limited to several kilo hertz, which considers as the main challenge for Underwater Acoustic (UWA) communications. Meanwhile, the Bit-Error-Rate (BER) performance of the UWA systems is degrades as a result of water temperature, water salinity, attenuation, and multi-path propagation. In this paper, we present a modification to the conventional Orthogonal Frequency Division Multiplexing (OFDM) based (FFT) using Fast Walsh–Hadamard transform (FWHT) instead of Fast Fourier Transform (FFT). Also, the proposed algorithm is encoded and decoded using Low Density Parity Check (LDPC) coding algorithm. Simulation results show that the proposed algorithm with LDPC coding can improve the BBER system performance than the corresponding traditional one.